The influence of audit committee characteristics on the ethical disclosure of sharia compliant companies - Peni Nugraheni; Syed Musa Alhabshi; Romzie Rosman (Cogent Business & Management, 2022)
The audit committee (AC) is an important mechanism within the corporate governance structure. Corporate misconduct and business failure have prompted greater scrutiny of the AC role. This study examines the effect of AC characteristics on disclosure, namely Islamic business conduct (IBC) disclosure, in sharia compliant companies (SCC) in Indonesia. SCC are expected to behave ethically and the AC can influence them by reviewing their internal control and stakeholder reporting systems. The study includes four AC characteristics as the independent variables, namely AC size, AC meeting frequency, AC gender diversity and AC expertise. The data were analysed using panel data regression. The samples comprised non-financial companies included in the Sharia Securities List on the Indonesia Stock Exchange for the years 2017-2020. The results show that the AC meeting variable had a positive effect on IBC disclosure. Meeting frequency can be used as a measurement of AC diligence, with the result showing that AC diligence in SCC can influence the disclosure of company ethical behaviour. The results of this study are expected to prompt Boards of Commissioners to encourage ACs to become more active in terms of undertaking more intense supervision and coordination so that the AC members can play a greater role in disclosing company information.
Keywords: 650; audit committee; ethics; Islamic business conduct; sharia compliant companies